Prussian Blue Nanozyme Normalizes Microenvironment to Delay Osteoporosis (Adv. Healthcare Mater. 19/2022). Issue 19 (5th October 2022) - Ye, Chenyi; Zhang, Wei; Zhao, Yongzheng; Zhang, Kai; Hou, Weiduo; Chen, Mo; Lu, Jinwei; Wu, Jianrong; He, Rongxin; Gao, Wei; Zheng, Yuanyi; Cai, Xiaojun
Abstract : Prussian Blue Nanoenzymes In article 2200787 by Rongxin He, Wei Gao, Xiaojun Cai and co‐workers, hollow Prussian blue nanozymes (HPBZs) significantly normalize the osteoporosis microenvironment, thereby inhibiting osteoclast formation and osteoclast resorption for treatment of osteoporosis, possibly owing to the suppression of the mitogen‐activated protein kinase and nuclear factor κ B signaling pathways.